2020
DOI: 10.1094/pdis-07-19-1473-re
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recombinase Polymerase Amplification Assay for DetectingMeloidogyne javanica

Abstract: Meloidogyne javanica is one of the most widespread and economically important nematodes in many countries, including China. In this study, a recombinase polymerase amplification (RPA) assay was evaluated for the detection of M. javanica based on the sequences of a sequence-characterized amplified regions marker gene segment. The RPA assay specifically detected M. javanica from individual juvenile or adult female, M. javanica-induced galls, and nematodes in the soil samples. The detection limit of M. javanica R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…For desinging the species-specific M. javanica RPA primers and probe we used a genome fragment firstly proposed by Randig et al (2002) and then applied for RPA assays by Ju et al (2019) and Chi et al (2020) . In our RPA assay the forward species-specific RPA primer proposed by Ju et al (2019) and a new reverse primer were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For desinging the species-specific M. javanica RPA primers and probe we used a genome fragment firstly proposed by Randig et al (2002) and then applied for RPA assays by Ju et al (2019) and Chi et al (2020) . In our RPA assay the forward species-specific RPA primer proposed by Ju et al (2019) and a new reverse primer were used.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, RPA assays with a gel visualization of amplicons for species diagnostics of M. javanica, M. arenaria, M. incognita and M. enterolobii have also been developed by Ju et al (2019) . Chi et al (2020) designed a rapid RPA assay for visual detection of M. javanica using SYBR Green and lateral flow dipsticks (LF-RPA) at endpoint. RPA assays for detection of the northern RKN, M. hapla were also developed by Song et al (2021) and Subbotin and Burbridge (2021) .…”
mentioning
confidence: 99%
“…Different RPA-based assays have been developed to successfully detect different pathogens from different specimen [18][19][20][21]. In the wake of the COVID-19 pandemic, RT-RPA has been adapted and used to amplify the envelope protein (E) and RNA-dependent RNA polymerase (RdRP) genes of SARS-CoV-2 successfully, showing a good sensitivity and specificity compared with RT-PCR [22].…”
Section: Recombinase Polymerase Amplificationmentioning
confidence: 99%
“…Using a lateral flow dipstick (LFD) strip, RPA amplicons can be observed directly with the naked eye, making it suitable for application in the field [13]. To date, RPA has been successfully used to detect a variety of plant parasitic nematodes [16], including Meloidogyne spp., such as M. incognita, M. arenaria, M. javanica, M. enterolobii [17], M. javanica [18], and M. enterolobii [19]. In addition, Cha et al reported the application of RPA for detecting Bursaphelenchus xylophilus [20,21].…”
Section: Introductionmentioning
confidence: 99%